Innovation in Procurement Processes: A Comparative Analysis of South Korea and Egypt - Makoni, Blessing (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to analyze the innovation in procurement processes: a comparative analysis of South Korea and Egypt. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: South Korea is highlighted for its advanced e-procurement systems, leveraging technology to enhance transparency, efficiency, and accountability. This has led to significant cost savings and improved supplier management. In contrast, Egypt, while making strides in modernizing procurement practices, faces challenges such as bureaucratic inefficiencies and limited technological adoption. Unique Contribution to Theory, Practice and Policy: Diffusion of innovations theory, the resource-based view (RBV) & institutional theory may be used to anchor future studies on innovation in procurement processes: a comparative analysis of South Korea and Egypt. Create a framework for exchanging best practices between South Korea and Egypt. Advocate for the development of a comprehensive policy framework that promotes innovation in procurement.